Breastfeeding Self-Efficacy, Mood, and Breastfeeding Outcomes among Primiparous Women. (August 2015) - Henshaw, Erin J.; Fried, Rachel; Siskind, Emily; Newhouse, Linda; Cooper, Marie
Background: A link between postpartum mood and breastfeeding has been established in the literature, but little is known about the relationship of breastfeeding self-efficacy (BSE) to breastfeeding and mood outcomes, particularly in primiparous women. Objectives: The purpose of this study was to prospectively evaluate the relationship among BSE, mood, and breastfeeding outcomes in primiparous women. A secondary purpose was to explore self-reported reasons for difficult emotional adjustment during the transition to motherhood. Methods: Primiparous women who initiated breastfeeding were surveyed at 2 days, 6 weeks, and 6 months postpartum. Breastfeeding self-efficacy, depressive symptoms, work status, breastfeeding difficulties, partner support, and use of lactation services were included in a hierarchical multiple regression analysis. Women who identified as emotionally distressed provided open-ended responses identifying the main cause of their stress. Results: High BSE at 2 days postpartum predicted positive emotional adjustment and fewer depressive symptoms at 6 weeks postpartum, as well as more exclusive breastfeeding at 6 months postpartum. Among distressed mothers, breastfeeding concerns were among the most commonly named reasons for stress, along with lack of sleep, lack of social support, and overwhelming learning demands involved with being a new parent. Conclusion: Breastfeeding perceptions are associated with emotional health and breastfeeding outcomes. Bolstering women's early BSE may be an important goal for multiple dimensions of postpartum health.